2018
DOI: 10.1016/j.jeurceramsoc.2018.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Molten salt synthesis of MAX phases in the Ti-Al-C system

Abstract: The molten salt method was used to synthesise the MAX phase compounds Ti2AlC and Ti3AlC2 from elemental powders. Between 900 1000 °C, Ti2AlC was formed alongside ancillary phases TiC and TiAl, which decreased in abundance with increasing synthesis temperature. Changing the stoichiometry and increasing the synthesis temperature to 1300 °C resulted in formation of Ti3AlC2 alongside Ti2AlC and TiC. The type of salt flux used had little effect on the product formation. The reaction pathway for Ti2AlC was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 16 publications
2
44
1
1
Order By: Relevance
“…Different synthesis routes with diverse outcomes were pursued and some of them (with purity values) are listed in Table 1. Solid‐state‐based synthesis routes such as reactive hot pressing, 7 reactive hot isostatic pressing, 5 solid‐liquid reaction synthesis, 8,9 reactive sintering, 10 pressureless sintering, 11,12 spark plasma sintering, 13 arc melting, 14 and self‐propagating high‐temperature synthesis (SHS) 15‐18 can be distinguished from ionic‐liquid medium‐assisted routes such as molten salt synthesis 19 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different synthesis routes with diverse outcomes were pursued and some of them (with purity values) are listed in Table 1. Solid‐state‐based synthesis routes such as reactive hot pressing, 7 reactive hot isostatic pressing, 5 solid‐liquid reaction synthesis, 8,9 reactive sintering, 10 pressureless sintering, 11,12 spark plasma sintering, 13 arc melting, 14 and self‐propagating high‐temperature synthesis (SHS) 15‐18 can be distinguished from ionic‐liquid medium‐assisted routes such as molten salt synthesis 19 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ti 2 AlC was synthesized by Galvin et al 19 using a molten salt method. They separately used NaCl, KCl, and a NaCl/KCl mixture as synthesis medium.…”
Section: Introductionmentioning
confidence: 99%
“…Some MAX phases (e.g. Ti3SiC2, Ti3AlC2, V2AlC, Cr2AlC) have been synthesized by molten salt method [24][25][26][27][28] . In the present work, we synthesized a MAX phase of Sc2SnC in molten salts environment where the Sc element belongs to rare earth.…”
mentioning
confidence: 99%
“…However, Ti 3 AlC 2 powder with a mean particle size of ∼ 100 nm is successfully synthesized at 950°C for 5 h when the mass ratio of the salt to 3Ti/Al/2C precursor materials is 10:1 as shown in the inset of Figure 2(d). To the best of our knowledge, the particle size of Ti 3 AlC 2 powder synthesized in this work is much smaller than that synthesized by traditional [14,15] and molten salt methods [25], which have been reported that plate-like and needle-like Ti 3 AlC 2 grains with a size of 5-10 and 5 μm were synthesized, respectively.…”
Section: Resultsmentioning
confidence: 69%
“…Furthermore, the amount of TiC and Ti 2 AlC phases reduces while the desired Ti 3 AlC 2 increases with increasing mass ratio of the salt to precursor materials as shown in diffractograms b and c, indicating that higher mass ratio of the salt to precursor materials is more conducive to Ti 3 AlC 2 formation. When the mass ratio of the salt to precursor materials increases to 10:1, the desired Ti 3 AlC 2 (96.7%) and a few TiC (3.3%) are obtained as shown in diffractogram d. These indicate that Ti 3 AlC 2 has been successfully synthesized from 3Ti/Al/2C precursor powders in NaCl-KCl molten salt with salt/precursor materials ratio of 10:1 and 6:1 at 950°C for 5 h. Additionally, it is reported that the plate-like and needle-like Ti 3 AlC 2 grains have been synthesized at 1300-1500°C and 1300°C, respectively, by traditional [14,15] and molten salt methods [25]. Therefore, the temperature of Ti 3 AlC 2 powder synthesized in this work is relatively lower, and the method is simpler and more efficient than that synthesized by traditional and molten salt methods.…”
Section: Resultsmentioning
confidence: 77%